UPAYA P2TP2A DALAM PERLINDUNGAN HUKUM TERHADAP KORBAN PEDOFILIA - Sa'dan, Saifuddin; Zubaidi, Zaiyad; Tinambunan, Zaidar (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
This research discusses the efforts made by P2TP2A in legal protection for child victims of pedophilia in Aceh Singkil. This research is motivated by the Indonesian Central Bureau of Statistics which records that pedophile crimes continue to increase. Not only in cities, but spreading to villages, one of which is Aceh Singkil. In victimology, children are very vulnerable to becoming victims of crime. Based on this, the guarantee of a decent life, the widest possible opportunity for children to grow and develop, both physically and mentally, is hampered due to the act of pedophilia and of course causes deep psychological trauma to the victim. The problem raised in this study is, What are the factors that cause pedophilia in Aceh Singkil? What are the efforts of P2TP2A Aceh Singkil for legal protection for child victims of pedophilia? aims to find out what are the factors causing the occurrence of pedophilia crimes in Aceh Singkil and the efforts made by P2TP2A Aceh Singkil for legal protection for child victims of pedophilia. The research method used in this study is descriptive analysis, with the type of research library research) and (field research). Based on the results of the research, the authors found that the factors causing the occurrence of pedophilia in Aceh Singkil were easy access to videos that contained elements of decency, alcohol, and a lack of strong faith, a lack of control over the family from parents as protectors, and a lack of education about sex against victim). There are several legal protection efforts carried out by P2TP2A Aceh Singkil, namely providing legal aid services, medical assistance, social rehabilitation efforts, reintegration and assisting all victim recovery referral mechanisms to the provincial P2TP2A.